FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA CABAI RAWIT DI PASAR NGABLAK, KABUPATEN MAGELANG - Fina, Fina; Yuliawati, Yuliawati (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
The aim of this study is to find out about the effect of distribution channel, substitution commodity price and consumer demand for cayenne pepper price in Ngablak Market, District of Magelang, Central Java. The sampling method used in this study was simple random sampling, in which 36 respondents were used. The type of this study is a descriptive quantitative. This study used a survey as the method by interviewing respondents in a research location. Data analysis used in this study was multiple linear regression. The result of this study shows that distribution channel and curly red chili price have real effect on cayenne pepper price on the other hand, consumer demand for cayenne pepper didn’t have any real effect on cayenne pepper price.